PENGEMBANGAN VIDEO PEMBELAJARAN BERBASISI PBL UNTUK MENDUKUNG KETERAMPILAN ABAD KE-21 MATERI REVOLUSI BUMI - Sa'diyah, Halimatus; Raida, Sulasfiana Alfi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Science instruction in junior high schools often faces challenges in explaining abstract topics such as the Earth's Revolution, while failing to meet the demands of 21st-century skills due to conventional media. This problem was addressed through research focused on developing innovative Problem-Based Learning (PBL)-based instructional videos for the Earth's Revolution, specifically designed to support the 4C skills. This research applied the ADDIE Research and Development (R&D) model, but its key stages were limited to the development stage. This process included analyzing student needs and the curriculum, designing video scenarios that adopted the PBL flow, and producing media that was then validated by material and media experts. The main findings showed that the resulting instructional video was declared